Capitalism and consumption : the case of Korean popular culture in Singapore - Lim, Syazana (2014)
This study examines the relationship between Korean popular culture and the hegemonic capitalist economic system; guided by the assumption that the former is a product of the latter, the capitalist substructure. Using the Frankfurt School theories, this study seeks to uncover the reasons why Singaporeans spend so much time and money on these cultural flows originating from South Korea. To this end, participant observations and in-depth interviews were carried out to understand the various consumption patterns and its possible effects on Singaporean’s lives. Through its findings, this study reveals two consumer typologies and features the consumption of Korean popular culture as having the potential to help Singaporeans cope with the demands of living in a fast-paced modern capitalist society.